A theoretical rationale for flexicurity policies based on education - Thomas Davoine (Institute for Advanced Studies (IHS), 2015)
The paper provides a theoretical rationale for flexicurity policies, which consist of low employment protection, generous unemployment insurance and active labor market programmes. It analyzes in which conditions flexicurity can be optimal. Low employment protection encourages costly education efforts to access high productivity and high innovation sectors, with firms more likely to survive and thus not exposing much their workers to unemployment risk. Activation programmes support the reallocation flow from unproductive to productive firms, helping to reduce unemployment. Low employment protection thus provides incentives for costly self-insurance against unemployment risk through education, mitigating the moral hazard cost of unemployment insurance and activation programmes. The paper provides realistic numerical illustrations where flexicurity is optimal, and where it is not optimal.
Keywords: J64; J65; J68; J32; H30; 330; flexicurity; unemployment insurance; job protection; active labor market policy; education